Принципи конституційно-правової відповідальності - Батанова, Н.М. (Альманах права, 2012)
У статті досліджуються теоретичні проблеми принципів конституційно-правової відповідальності. Визначається поняття принципів конституційно-правової відповідальності, виділяються та характеризуються їх основні види. В статье исследуются теоретические проблемы принципов конституционно-правовой ответственности, выделяются и характеризуются их основные виды. There are researched theoretical issues of constitutional and legal responsibility principles.The concept of principles of constitutional and legal responsibility as fundamental ideas of constitutional law that reflected the nature, purpose and content of the constitutional and legal responsibility and patterns of its development and realization is defined. The basic principles of constitutional and legal liability include: principles of justice, humanity, legitimacy, inevitability, guilty of an act. The study of the principles of constitutional and legal responsibilities are important direction of modern science of constitutional law, which aims at developing an integrated concept of constitutional and legal responsibility, improvement of legislative regulation and effective implementation in practice.